Dynamic pigmentary and structural coloration within cephalopod chromatophore organs - Thomas L. Williams (Nature Portfolio, 2019)
Chromatophores in cephalopod skin are known for fast changes in coloration due to light-scattering pigment granules. Here, authors demonstrate structural coloration facilitated by reflectin in sheath cells and offer insights into the interplay between structural and pigmentary coloration elements.